THE SEMIOTIC REFLECTIONS ABOUT THEATRICAL COSTUMES (ON EXAMPLE OF V.FURYK COSTUMES FOR “JOHANNA, THE WIFE OF HOOSA” BY LESJA UKRAINKA) - Цимбалюк, О. К. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The author examines costumes from philosophical point of view as semant-semiot image helps to clarity a mystery of human communication.